Polysaccharides-Rich Extract From Fruiting Body Of Mushroom (Pleurotus Pulmonarius) As A Potential Source Of Prebiotic - Leow, Kim Teck (2020)
Prebiotic is capable to modulate the composition of beneficial gut microbiota for disease prevention and immunomodulation of the host. Prebiotic potential of polysaccharides-rich extract (PRE) from Pleurotus pulmonarius is unknown. Research was carried out to determine the physicochemical properties and prebiotic characteristics of PRE, and to assess the synbiotic relationship of PRE with Lactobacillus acidophilus FTDC3871 (La3871) and PRE with Lactobacillus bulgaricus FTDC1511 (Lb1511). The PRE contained 71.9% of polysaccharides which consisted of D-galactose and D-glucose at a molar ratio of 1.4:1.0. The percentage of non-glucan polysaccharides, β-glucan and α-1,4-linked glucan were 40.6%, 23.5% and 7.8% respectively. The non-polysaccharides components were moisture (5.48%), protein (1.94%), reducing sugars (0.2%), ash and others (20.48%). The Mw, Mn and polydispersity index (Mw/Mn) of the purified mushroom polysaccharides was 5.86 x 105 Da, 4.23 x 105 Da and 1.385 respectively. The mushroom PRE was resistant to in vitro acid hydrolysis in the stomach, and when subjected to hydrolysis by pancreatic juice at pH 6.0, 7.0, and 8.0, PRE was hydrolyzed in the range of 10.3% to 13.8%. From a total of 12 strains of lactic acid bacteria tested, growth of 5 strains (La3871, Lb1511, L. casei FTCC0442, L. plantarum FTCC0350 and Bifidobacterium longum FTDC8133) on PRE was better than on blank medium, and also equivalent to medium added with inulin. Positive prebiotic activity scores (p<0.05) were obtained when La3871 (+0.16), Lb1511 (+0.14), Bifidobacterium longum FTDC8133 (+0.12) and Lactobacillus plantarum FTCC0350 (+0.07) were cultivated on PRE. La3871 could ferment PRE more efficiently than Lb1511. When La3871 and Lb1511 were cultivated on PRE for 24 h respectively, the PRE assimilation rate, PRE utilization, pH reduction, total organic acids were (0.28 mg per mL per h, 0.11 mg per mL per h), (26.3%, 15.5%), (0.19-0.37, 0.10-0.27) and (33.81 mM, 18.27 mM) respectively. La3871 and Lb1511 demonstrated homo-fermentative characteristics in medium added with glucose, but shifted towards the hetero-fermentative fermentation when MRS basal medium was added with PRE. When La3871 and Lb1511 was incubated on PRE for 12-72 h, polysaccharides degrading enzyme activity was detected, with their specific activity at 3.86-4.63 and 1.09-2.95 U/mg protein respectively. Data also indicated that the presence of PRE in growth medium is necessary to induce production of polysaccharides degrading enzymes by La3871 and Lb1511. In conclusion, PRE exhibited potential prebiotic characteristics and seem to selectively enhance the growth of La3871 than most of lactic acid bacteria strains tested